Real world outcomes in platinum sensitive relapsed ovarian, fallopian tube, or peritoneal cancer treated in routine clinical practice in the United Kingdom prior to poly-ADP ribose polymerase inhibitors. Issue 7 (21st April 2020) - Lord, Rosemary; Rauniyar, Jyoti; Morris, Tamsin; Condon, Orlaith; Jones, Rachel; Miller, Rowan; Hall, Marcia; Lofts, Fiona; Glasspool, Rosalind M; Hudson, Emma
Abstract : Introduction: The introduction of poly-ADP ribose polymerase inhibitors in ovarian cancer has demonstrated significantly improved progression free survival in four randomized controlled clinical trials in patients with platinum sensitive relapsed ovarian cancer. While overall survival data remain immature, this real world evidence study sets a baseline for future evaluation of poly-ADP ribose polymerase inhibitors. Methods: A retrospective chart review was undertaken to investigate real world survival outcomes across 13 National Health Service Trusts in England, Wales, and Scotland. Patients were included if they had platinum sensitive relapsed high grade serous ovarian cancer and had responded to secondline platinum based chemotherapy. Clinical data were collected retrospectively from electronic prescribing records and chart notes. The index date for overall survival analysis was defined as the later of (1) day 1 of the final secondline platinum based treatment or (2) date of response to secondline treatment. The primary objective was overall survival from the index date. Secondary objectives included progression free survival and overall survival by subsequent line of treatment. BRCA mutation status was collected where available. Quality of life questionnaires were not assessed within this study. Results: 233 patients were identified who met the study inclusion criteria. Patient characteristics were consistent with other published data, with a median age of 61 years (range 35–85). Sensitivity analysis of the primary objective demonstrated that the earliest point poly-ADP ribose polymerase inhibitors may be initiated (following completion of secondline chemotherapy) is associated with a median overall survival of 19.8 months. Secondline median overall survival and progression free survival from the index date were 19.3±2.4 months and 7.3±1.2 months, respectively. 144 patients were treated with thirdline chemotherapy with median overall survival and progression free survival from the index date (either date of last cycle of thirdline treatment or date of response to thirdline treatment) of 8.3±2.6 and 4.4±1.8 months, respectively. Conclusion: Overall survival was shown to be shorter in this real world study compared with randomized clinical trials, and underlines the differences in clinical outcomes of patients in a real life setting. This baseline real world study has demonstrated poor survival outcomes in this patient group prior to availability of poly-ADP ribose polymerase inhibitors.